A guide to historic missions and church[e]s of the Arizona-Sonora borderlands - Morgan, Richard J. (Adventures in Education, Inc., 1995)
A comprehensive guide to the missions constructed by Jesuits and Franciscans in a region colonized by Spain and since divided between the United States and Mexico provides an historical synopsis of the period, a description of the physical and cultural characters of the region at the time of the missionaries' arrival, and an explanation of the architectural features incorporated into the construction of their missions and churches